2017
DOI: 10.4103/jrpp.jrpp_17_49
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin supplementation may improve the outcome of patients with hemorrhagic stroke in the intensive care unit

Abstract: Objective:Although mechanical ventilation is frequently a life-saving therapy, its use can result in unwanted side effects. It has been well documented that the choice of sedating agent may influence the duration of mechanical ventilation. Melatonin is a sedative and analgesic agent without any respiratory depressant effect which makes it an attractive adjuvant for sedation in the intubated patients. The aim of this study is to evaluate the effect of melatonin on the duration of mechanical ventilation in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…The effectiveness of exogenous melatonin for the treatment of sleep disturbance [ 13 ], as antioxidant [ 14 ], antianxiety agent like benzodiazepine action has been established in many studies [ 13 , 15 , 16 ]. Furthermore, different from the conventional sedative agents, this hormone does not deteriorate nighttime hypoxemia or ventilator responses [ 17 – 19 ]. Besides, it has been shown that melatonin can treat and avoid ICU delirium [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effectiveness of exogenous melatonin for the treatment of sleep disturbance [ 13 ], as antioxidant [ 14 ], antianxiety agent like benzodiazepine action has been established in many studies [ 13 , 15 , 16 ]. Furthermore, different from the conventional sedative agents, this hormone does not deteriorate nighttime hypoxemia or ventilator responses [ 17 – 19 ]. Besides, it has been shown that melatonin can treat and avoid ICU delirium [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a neuroprotective agent with sedative, hypnotic, and analgesic properties and without any respiratory depressant effect which makes it a suitable adjuvant for sedation in the ICU [ 17 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dianatkhah et al reported a decreased length of ICU stay, length of MV and mortality in 40 intubated hemorrhagic stroke patients treated with high-dose melatonin (30mg). ( 26 ) However, these large doses have not been studied extensively and are currently not deemed safe. These results were not reproduced in further larger RCTs, such as Abbasi et al, Gandolfi et al or our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, melatonin alleviates circadian disturbances and improves sleep, increasing delta power and decreasing sleep fragmentation in rats after an induced stroke [ 166 ]. In clinical settings, melatonin supplementation was associated with a lower risk of post-stroke delirium (a single dose of 2 mg/day at 20:00 within the first 24 h of ischemic stroke onset) compared to the control group [ 167 ] and with the shorter duration of mechanical ventilation and length of stay in the intensive care unit in a cohort of patients with hemorrhagic stroke (30 mg melatonin every night during a stay at the intensive care unit) [ 168 ]. In early and late rehabilitation periods, melatonin administration (3 mg daily for 3 months) led to an increase in the BDNF level that correlated with improved sleep, emotional status, and quality of life [ 169 , 170 ].…”
Section: Circadian System and Treatment Developments In Strokementioning
confidence: 99%